1, 8‐Disubstituted Xanthylidene‐Based Remote Carbenes: Photolytic Generation and Isolation of Low‐Coordinate Palladium(II) Complex. Issue 3 (18th December 2014) - Sugawara, Shun; Abe, Manabu; Fujiwara, Yoshihisa; Wakioka, Masayuki; Ozawa, Fumiyuki; Yamamoto, Yohsuke
Abstract: The isolation and study of carbenes with σ‐donating and π‐accepting properties stronger than those of N‐heterocyclic carbenes (NHCs) have been regarded as one of the big challenges in carbene chemistry. We have investigated the properties of 1, 8‐disubstituted xanthylidene‐based compounds by using two different approaches: The photolysis‐induced formation of free carbenes and the synthesis of the corresponding metal–carbene complexes by oxidative addition. The former study revealed that the carbene unsubstituted at the 1‐ and 8‐positions is kinetically more reactive than the parent xanthylidene and that the substituents at the 1‐ and 8‐positions are less effective in generating carbenes by photolysis. However, oxidative addition of palladium(0) to the 1, 8‐diphenyl‐substituted precursor successfully afforded a low‐coordinate 14‐electron palladium(II)–carbene complex. This unusual complex is stabilized by agnostic interactions involving an adjacent phenyl group. This complex is the second example of a stable cationic 14‐electron palladium(II)–carbene complex to have been reported so far. Abstract : The photolysis‐induced formation of 1, 8‐disubstituted xanthylidene‐based remote carbenes from tosylhydrazone lithium salts has been investigated. The 1, 8‐unsubstituted carbene was found to be kinetically more reactive than the parent xanthylidene. Oxidative addition of palladium(0) to the chloride precursor facilitated the isolation of a low‐coordinate 14‐electron palladium(II)–carbene complex.